Influence of interaction between organic cation and inorganic unit in bi-based hybrid perovskites for photoelectronic properties. Issue 12 (December 2022) - Han, Liuyuan; Wu, Qian; Lei, Longfei; Chen, Jinghang; Xue, Ni
Abstract: With the increase of the passion on lead-free perovskites, more and more endeavor focused on halobismuthates. Here, we have introduced the p -iodoaniline and p -phenylenediamine into Bi-based hybrid materials, and two photoactive iodobismuthate named p -phenylenediamine iodobismuthate (PDABI) and p -iodoaniline iodobismuthate (PIDBI) were prepared. Their single structures, band gaps, thermostability and other properties were explored. The structure results revealed that they all have 1D BiI4 - anion chains with edge-shared BiI6 octahedron. The DFT result revealed that PIDBI had an inherent interaction between the I substituent in p -iodoaniline cation and the Bi atom in inorganic BiI4 - anion chains. The photodetector assembled by PDABI and PIDBI revealed that the interaction provided by symmetric p -phenylenediamine has a positive effect on PIDBI's optoelectronic properties compared to the role of asymmetric p -iodoaniline in PDABI. Abstract : Organic-inorganic hybrid; DFT; Crystal structure; Halobismuthate.